Efektivitas Kernel Kelor dan Ampas Kernel Kelor (Moringa oleifera L.) sebagai Biokoagulan dan Desinfektan Alami pada Pengolahan Air Sungai - Irmayanti Irmayanti; Chairil Anwar; Ika Rezvani Aprita (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2019)
his study specifically aims to study the effectiveness of Moringa oleifera L. Moringa oleifera seed powder as a biocoagulant and disinfectant for river water treatment. This study use a factorial randomized block design (RBD) with four replications. The treatment in this study consisted of 2 factors, the variation factor of biocoagulants (v) and the biooagulants concentration (k). Moringa seed variation factor consists of 2 levels, namely Moringa seed powder (v1) and Moringa seed pulp (v2) powder, the factor of Moringa seed powder concentration and Moringa seed pulp powder consists of 3 levels, namely 0.025% (k1), 0.05 % (k2) and 0.075% (k3). Analysis carried out on river water, treated water and water after screening included pH, color, turbidity, manganese (Mn), iron (Fe) and total coli bacteria. The best quality processed water is treated with Moringa (v1) seed powder with a concentration of 0.05% (k2) with the following characteristics: pH 7.21, color 11.25 TCU (True Color Units), turbidity 2.38 NTU (Nephelometric Turbidity Units), manganese (Mn) levels 0.022 mg.L-1, iron content 0.036 mg.L-1, and coli bacteria total 0.08 x 102/100 ml samples